Phylogenetics and taxonomy of Habenaria sect. Micranthae (Orchidaceae), with the description of an overlooked new species from the Espinhaço mountain range, Eastern Brazil. Issue 1 (31st December 2022) - Cruz-Lustre, Gabriela; Castro, Cristian; Borba, Eduardo Leite; Batista, João Aguiar Nogueira
Abstract : Habenaria sect. Micranthae is one of the 14 Neotropical sections of the genus and in its current delimitation, comprises 14 morphologically heterogeneous species. Previous phylogenetic analyses have shown that the section is polyphyletic, so that both the species composition and the morphological characterization of the section are undefined. Furthermore, among the species associated with the section, H. bahiensis has a long history of obscure taxonomic identity and H. gollmeri of undefined phylogenetic relationships. To revise the taxonomic and morphological circumscription of H . sect. Micranthae and clarify the identity of H. bahiensis and phylogenetic relationships of both these species, we collected fresh samples to generate new sequences of DNA markers (ETS, ITS, matK-trnK, and rps16-trnK ), performed Bayesian and parsimony analyses, and reassessed morphological features. Based on our analyses, H. sect. Micranthae is re-circumscribed to include eight phylogenetically and morphologically related species, characterized by their sulcate viscidia. Our results indicate that H. gollmeri belongs to H. sect. Micranthae and to the H. parviflora clade. Because none of the samples collected or examined exactly matched the original description of H. bahiensis, the identity of this species remains elusive. Specimens from the Espinhaço mountain range, previously identified as H. bahiensis, represent a new species described here as H. abscondita . In addition, we lectotypified H. maderoi and H. moritzii and proposed the synonymization of this last species with H. armata .